Red cell ion transport abnormalities in experimental hypertension - Zicha, J (Fundamental & clinical pharmacology, 1993)
The original attractive hypothesis on the important role of elevated cell Na+ concentration in the pathogenesis of hypertension stimulated a search for generalized membrane defects and ion transport abnormalities in various easily accessible cells including erythrocytes. An attempt is made here to compare this hypothesis with the data on red cell ion transport alterations that were observed in experimental hypertension over the last 15 years. Several methodological (presence of extracellular Na+ in incubation media, kinetic approach to the evaluation of transport systems) and physiological problems (potassium depletion, age-dependent changes) are discussed in more detail because they can substantially modify the results obtained. Available data suggest a possible contribution of augmented Na+ leak to the development of both genetic and salt-dependent experimental hypertension. The role of alterations in the activity of the Na(+)-K+ pump or the Na(+)-K+ cotransport system still remains unclear.
Keywords: iontový transport; Disease Models, Animal; erytrocyty; Erythrocytes; Rats, Inbred SHR; modely nemocí na zvířatech; krysa rodu Rattus; potkani inbrední SHR; potkani inbrední WKY; sodíko-draslíková ATPasa; hypertenze; Animals; Ion Transport; Rats, Inbred WKY; Sodium-Potassium-Exchanging ATPase; Hypertension; zvířata; Rats